ANALISIS USABILITY SITUS WEB PUSAT DOKUMENTASI SASTRA HB JASSIN USABILITY ANALYSIS OF HB JASSIN LITERATURE DOCUMENTATION CENTER WEBSITE - Mugabe, Robert; Utomo, R. Drajatno Widi; Jasjfi, Elda Franzia (Universitas Trisakti, 2021)
Abstract Digitalization is an effort to save the text from being destroyed due to hostile climate and humidity. Therefore, observers, enthusiasts, researchers and script owners as well as the government must unite to build synergies in saving and maintaining the script. Thus, the digitalization program which is currently being promoted by various parties or agencies can truly save the nation's intellectual treasure contained in the text. At least, HB Jassin's Literary Documentation Center can take the lead in digitizing theater scripts. With the involvement of the textbook community and official state institutions, it is hoped that there will be some kind of website that takes into account its use as a form of digitization as a form of sustainable national preservation of theater scripts.Keywords: digitalization, teather manuscripts, Center for Literary Documentation of HB Jassin, usability. AbstrakDigitalisasi merupakan sebuah upaya penyelamatan naskah dari kemusnahan akibat iklim dan kelembaban udara yang tidak bersahabat. Oleh karena itu, para pemerhati, peminat, peneliti, dan pemilik naskah serta pemerintah harus bersatu padu untuk membangun sinergi dalam hal penyelamatan dan pemeliharaan naskah. Dengan demikian, program digitalisasi yang kini sedang digalakkan oleh berbagai pihak atau instansi benar-benar dapat menyelamatkan khazanah intelektual bangsa yang terkandung di dalam naskah. Setidaknya, Pusat Dokumentasi Sastra HB Jassin dapat tampil sebagai garda depan dalam urusan digitalisasi naskah teater. Dengan pelibatan komunitas pernaskahan dan lembaga resmi negara, diharapkan adanya semacam situs web yang memerhatikan usability sebagai bentuk digitalisasi sebagai wujud penyelamatan naskah teater secara nasional yang berkesinambungan.Kata kunci: digitalisasi, naskah teater, Pusat Dokumentasi Sastra HB Jassin, usability.